Calcium Phosphate‐Reinforced Metal‐Organic Frameworks Regulate Adenosine‐Mediated Immunosuppression - Liang, Ling; Yang, Lei‐Lei; Wang, Wenjie; Ji, Cailing; Zhang, Lei; Jia, Yiyi; Chen, Yuxia; Wang, Xueqiang; Tan, Jie; Sun, Zhi‐Jun; Yuan, Quan; Tan, Weihong (Advanced materials (Weinheim), 2021)
Long‐term accumulation of adenosine (Ado) in tumor tissues helps to establish the immunosuppressive tumor microenvironment and to promote tumor development. Regulation of Ado metabolism is particularly pivotal for blocking Ado‐mediated immunosuppression. The activity of adenosine kinase (ADK) for catalyzing the phosphorylation of Ado plays an essential role in regulating Ado metabolism. Specifically, accumulated Ado in the tumor microenvironment occupies the active site of ADK, inhibiting the phosphorylation of Ado. Phosphate can protect ADK from inactivation and restore the activity of ADK. Herein, calcium phosphate‐reinforced iron‐based metal‐organic frameworks (CaP@Fe‐MOFs) are designed to reduce Ado accumulation and to inhibit Ado‐mediated immunosuppressive response in the tumor microenvironment. CaP@Fe‐MOFs are found to regulate the Ado metabolism by promoting ADK‐mediated phosphorylation and relieving the hypoxic tumor microenvironment. Moreover, CaP@Fe‐MOFs can enhance the antitumor immune response via Ado regulation, including the increase of T lymphocytes and dendritic cells and the decrease of regulatory T lymphocytes. Finally, CaP@Fe‐MOFs are used for cancer treatment in mice, alleviating the Ado‐mediated immunosuppressive response and achieving tumor suppression. This study may offer a general strategy for blocking the Ado‐mediated immunosuppression in the tumor microenvironment and further for enhancing the immunotherapy efficacy in vivo. Calcium‐phosphate‐reinforced iron‐based metal–organic frameworks (CaP@Fe‐MOFs) are designed to reduce adenosine accumulation and to inhibit adenosine‐mediated immunosuppressive response. CaP@Fe‐MOFs regulate the adenosine metabolism by promoting adenosine‐kinase‐mediated phosphorylation and relieving the hypoxic tumor microenvironment. Moreover, CaP@Fe‐MOFs enhance the antitumor immune response via adenosine regulation, including the increase of T lymphocytes and dendritic cells and the decrease of regulatory T lymphocytes.